Berlioz's Orchestration Treatise: A Translation and Commentary - Berlioz, Hector 1803-1869; Macdonald, Hugh (Cambridge Cambridge University Press, 2002)
Berlioz's Orchestration Treatise (1843) is a classic textbook by a master of the orchestra, which has not been available in English translation for over a century. This is a book by and about Berlioz, since it provides not only a new translation but also an extensive commentary on his text, dealing with the instruments of Berlioz's time and comparing his instruction with his practice. It is thus a study of the high craft of the most distinctive orchestrator of the nineteenth century.
Keywords: 19th Century (1801-1900); Orchestration; Instrumentation; France